Sprouted All Around: The Emergence and Evolution of Housing Estates in Brussels, Belgium - Costa, Rafael; de Valk, Helga (Springer Open, 2018)
The purpose of the study is to investigate the socioeconomic evolution of large housing estates in Brussels, Belgium, in particular their role in shaping residential segregation in the city. As in many European countries, modernist and functionalist ideas of the mid-twentieth century led to the raising of large housing estates in Brussels, in an attempt to offer middle-class households affordable yet modern and comfortable dwellings. However, contrary to other countries, the development in Belgium was marked by general housing policies that promoted homeownership, with limited investment in social housing, and a lack of laws and political vision related to spatial planning Whereas some public ensembles were conceived by modernist architects, most of Brussels large housing estates were built by private contractors in peripheral neighbourhoods and were aimed at homeownership of the lower middle class. In the chapter presents a brief historical perspective of the policies, ideologies and territorial processes that made it possible for housing estates to develop and spread in Brussels. Next, the authors analyse how large housing estates evolved since the 1990s in terms of socioeconomic composition and the role they play in segregation. Finally the aouthors discuss the challenges, current perspectives and political awareness with respect to large housing estate. The findings point out that Brussels housing estates are spatially scattered and have only a limited impact on the concentration of deprivation and foreign nationals. However, the trends identified in the study indicate that housing estates can become important socioeconomic fractures at the local level.
Keywords: Wohnungswesen; Wohnungspolitik; Sozialer Wohnungsbau; Segregation; Wohnsiedlung